(untitled) (Conferencea, 2024)
To identify incorrect or suspicious actions and operations in voluntary web applications connected to the e-government system, it is necessary to have documented and regulated standards for monitoring and analyzing log entries, network activities and operations. This article discusses the use of information security in the e-government system to detect illegal actions monitoring is proposed.